Traditions of Welcoming Islamic Holidays Case Studyo of the Transformation of the Hagaf Tradition in Gunting Saga, Labuhan Batu Utara, 2000-Present - Humaerah, Humaerah; Paralihan, Hotmatua (Journal La Sociale, 2025)
HaGAF (Happy Aidilfitri Day) is a local cultural heritage of the Gunting Saga Village community, North Labuhanbatu Regency, which has since its inception served as a medium for religious and social expression in celebrating Eid al-Fitr. However, the acceleration of globalization, the penetration of popular culture, and lifestyle changes especially among the younger generation have driven a significant transformation of this tradition. This study aims to analyze the form of HaGAF transformation, identify its driving factors, and examine the role of the local community and government in its preservation. Using a qualitative approach with participatory observation, in-depth interviews, and documentation techniques, this study found that HaGAF has evolved from a traditional, ritual-based celebration into a more inclusive and modern festival, encompassing a music festival, a digital content competition, and an e-sports tournament. Despite this modernization, traditional elements remain intact through the involvement of the younger generation and the promotion of cultural values via social media. The local government plays a crucial role in supporting the sustainability of this tradition by granting permits and securing events. Theoretically, these findings reinforce Clifford Geertz's view that culture is a dynamic system of meaning that is continually reinterpreted according to changing social contexts. On the contrary, these results challenge the structural-functional approach as proposed by Bronislaw Malinowski and Talcott Parsons which tends to see tradition as a stable component in the social system to maintain order, often ignoring the internal adaptation and progress of culture.